KONSEP WAHYU DALAM ALQURAN (KAJIAN SEMANTIK) - Arief Muammar (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2017)
For prophets who are at a lower level, angels descending to them both in the conscious or dream world, will dwell in their imaginary power and the supernatural nature (revelation) which descends from the Hadhrat miah Scientific will reach their hearts. But for the Prophets who have a position higher than q uqul and angels, the delivery of revelation and the descent and descent of angels will be realized with the permission of the Nafs Nabawi. They can witness and dialogue directly with the angels especially with the angel Jibril witnessed in “the nature of 'uqul” with the form of